(untitled) (Journal of Engineering, 2013)
Trickle bed reactor was used to study the hydrogenation of nitrobenzene over Ni/SiO2 catalyst. The catalyst was prepared using the Highly Dispersed Catalyst (HDC) technique. Porous silica particles (capped cylinders, 6x5.5 mm) were used as catalyst support. The catalyst was characterized by TPR, BET surface area and pore volume, X-ray diffraction, and Raman Spectra. The trickle bed reactor was packed with catalyst and diluted with fine glass beads in order to decrease the external effects such as mass transfer, heat transfer and wall effect. The catalyst bed dilution was found to double the liquid holdup, which increased the catalyst wetting and hence, the gas-liquid mass transfer rate. The main product of the hydrogenation reaction of nitrobenzene was aniline. Reaction operating conditions, i.e., temperature, liquid flow rate, and initial feed concentration were investigated to find their influences on the conversion and rate of nitrobenzene hydrogenation. Under normal conditions without bed dilution, the system was mass transfer controlled. In the diluted reactor, on the other hand, the resistance of mass transfer was nearly absent and the system became under surface kinetic control. The catalyst showed significant deactivation during the reaction period due to the adsorption of intermediate amine products on the surface of the catalyst. The kinetic study revealed that the reaction is zero order with respect to nitrobenzene concentration for the range of concentration between 0.58 to 1.17 mol/L while it was of positive order for the initial concentration less than 0.58 mol/L